Analyzing the Locus of Soft Spheres: Illustrative Cases and Drawings (European Journal of Pure and Applied Mathematics, 2018)
In the studies that have been carried out so far, the definition of soft sphere has been made, although it has been accepted very hard to revive it mathematically. In this study, the differences among soft real numbers and soft points are used for the first time to revive the soft sphere mathematically thus the locus of the soft sphere can be analyzed. Applications of soft spheres are supported by suitable examples to discuss the locus of them with scrupulous attention to detail.